Enhancing Hard Anodization ff Aluminum 1100 using Variated Concentration and Aeration in 20% Sulfuric and Phosphoric Acid Electrolytes - Leoanggraini, Unung; Yusuf, Yusmardhany; Nugraha, Ganjar; Samuel, Samuel; Sarip, Fahmi Haddad; Trirahayu, Dhyna Analyes; Sihombing, Rony (Journal of Green Science and Technology, 2024)
Aluminum is widely used in manufacturing, especially in automotive and aerospace, due to its light weight and easy form, although it is worn. The purpose of this research is to get the highest layer formation efficiency. During the application, hard anodizing creates a new layer in the form of a anatural protective layer on the metal surface. In hard anodized aluminum, the specimen sanded, degreasing with base, and acid neutralization. Then, hard anodizing is performed by connecting the workpiece to the positive pole and the cathode to the negative pole with a current density of 3A/dm² for 30 minutes in an electrolyte solution at a temperature of 5°C. The variations used are the mixture composition between sulfuric acid (concentration 15% - 20%) and low concentration phosphoric acid (0%, 1%, 2%, 3%, 4%, 5%) which are differentiated into aerated and non-aerated systems. Then weigh the anodized work piece to determine the weight gain of the metal due to the formed layer. The weight of the obtained layer is used to determine the efficiency of the formation of oxide layer.  The best layer formation efficiency is found in the sulfuric acid - phosphoric acid concentration variation (15% - 1%) in the aerated system at 73.47%. While the non aerated system at 73.28%. The aerated condition shows superior results compared to the non-aerated system, yielding better efficiency values than the non-aerated system.  Keywords: Aluminum 1100, Hard Anodizing, Mechanical Properties, Aeration, Electrolyte